2014
DOI: 10.1007/s11224-014-0495-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and kinetics of low-temperature oxidation of a biodiesel surrogate−methyl acetate radicals with molecular oxygen

Abstract: Accurate description of reactions between methyl acetate (MA) radicals and molecular oxygen is an essential prerequisite for understanding as well as modeling low-temperature oxidation and/or ignition of MA, a small biodiesel surrogate, because their multiple reaction pathways either accelerate the oxidation process via chain branching or inhibit it by forming relatively stable products. The accurate composite CBS-QB3 level of theory was used to explore potential energy surfaces for MA radicals ? O 2 system. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 45 publications
7
31
0
Order By: Relevance
“…The results of a theoretical study of the kinetics of the reaction between methyl acetate radicals and O 2 were reported by Mai et al [111]. The calculated results were in accord with the literature data.…”
Section: Issuesupporting
confidence: 83%
“…The results of a theoretical study of the kinetics of the reaction between methyl acetate radicals and O 2 were reported by Mai et al [111]. The calculated results were in accord with the literature data.…”
Section: Issuesupporting
confidence: 83%
“…The geometry optimization and frequency calculations employ the hybrid density functional theory, namely, the B3LYP/CBSB7 level of theory. Found to be suitable for investigating the detailed kinetics of the similar reactions of methyl propionate radicals /methyl acetate radicals with an O 2 molecule, the composite method CBS-QB3, based on the B3LYP/CBSB7 geometry, was used to obtain the energies of all species involved.…”
Section: Computational Methodologymentioning
confidence: 99%
“…14 The geometry optimization and frequency calculations employ the hybrid density functional theory, namely, the B3LYP/CBSB7 15−17 level of theory. Found to be suitable for investigating the detailed kinetics of the similar reactions of methyl propionate radicals 18 /methyl acetate radicals 19 with an O 2 molecule, the composite method CBS-QB3, 20 based on the B3LYP/CBSB7 geometry, was used to obtain the energies of all species involved. The HIR corrections were thoroughly taken into account in thermodynamic/kinetic calculations, in which the hindrance potentials of the rotation along the C−C and C−O "single" bonds were calculated at the B3LYP/CBSB7 level via relaxed surface scans (cf.…”
Section: ■ Computational Methodologymentioning
confidence: 99%
“…Surrogates are typically used to emulate the physical and chemical properties of real conventional fuels that are too complicated for detailed investigation. Many investigations have been performed to study combustion-related processes of surrogate-biodiesel molecules, most of which are saturated methyl ester and ethyl esters. Currently, there are some studies (e.g., Lai et al, , Wang et al, , Zhang et al, Das et al, Lin et al, and Kumar et al) in which theoretical mechanisms for biodiesel combustion have been developed. However, in those mechanisms, the rate constant assignment, which is based on limited sets of available rate constants, has certainly introduced considerable uncertainty to the rate constants.…”
Section: Introductionmentioning
confidence: 99%
“…Low-temperature combustion, which has potential to improve engine efficiency and reduce toxic emissions, has received much attention in developing oxidation of biodiesel surrogate systems. , All these studies pointed out that mechanisms and kinetics of low-temperature oxidation of biodiesel only involve a few crucial reaction channels such as the following: (i) alkyl methyl/ethyl ester peroxy (RO 2 • ) radicals, including dissociation (RO 2 • → R • + O 2 ), concerted elimination (RO 2 • → ester olefin + HO 2 ), and isomerization to form the hydroperoxy alkyl methyl/ethyl ester radical (RO 2 • → • ROOH); and (ii) hydroperoxy alkyl methyl/ethyl ester ( • ROOH) radicals, including β-scission to form olefin ester and HO 2 ( • ROOH → olefin ester + HO 2 ), ketone/aldehyde ester formation ( • ROOH → ketone/aldehyde ester + OH), and cyclic ether ester formation ( • ROOH → cyclic ether/ester + OH) , (cf. Figure for a summary of these important channels).…”
Section: Introductionmentioning
confidence: 99%